Disentangling the effects of large minimum wage and VAT changes on prices: Evidence from Mexico - Mariana Calderón Cerbón; Josué Fernando Cortés Espada; Jorge Pérez Pérez; Alejandrina Salcedo (Banco de México, 2022)
In January 2019, the authorities increased the minimum wage and decreased the valueadded tax (VAT) in an effort to boost activity on the northern Mexican border. In this paper we estimate the effects of both policies on prices. We find that the upward pressures on prices due to the minimum wage hike were more than offset by the downward pressures associated with the VAT. In the absence of the VAT reduction policy, average prices in the northern Mexican border would have been higher. We estimate that the effects of the minimum wage on prices tended to be smaller for goods or services produced with a larger share of informal labor.
Keywords: J38; J46; H20; 330; Minimum wage; Value-Added Tax; Prices